Prevalence and Risk Factors of Musculoskeletal Disorders Among Nurses: A Systematic Literature Review - Heni Fa'riatul Aeni; Evi Widowati; Oktia Woro Kasmini Handayani (Jurnal Ilmu Kesehatan Masyarakat, 2025)
Musculoskeletal disorders (MSDs) are considered a leading cause of occupational disability worldwide, especially among nurses who have a high risk due to heavy workloads and repetitive manual handling of materials. This systematic review synthesizes recent evidence (2015–2024) regarding the prevalence, risk factors, and assessment methods of MSDs among nurses. Based on PRISMA 2020 guidelines, studies published between 1 January 2015 and 31 December 2024 were searched in Scopus, Web of Science, PubMed, and ScienceDirect. Two independent reviewers screened and assessed methodological quality using the Critical Appraisal Skills Program (CASP) checklist. Ten studies from eight countries met the inclusion criteria. Data were synthesized narratively, supported by quantitative summaries of prevalence and risk factors. The prevalence of MSDs among nurses ranged from 31.6% to 97.3%, with the main effects on the lower back, neck, and shoulders. Nordic Musculoskeletal Questionnaire (NMQ), Nordic Body Map (NBM), and Quick Exposure Check (QEC) were applied as the assessment tools. Major risk factors included awkward posture, prolonged standing, high workload, and psychosocial stressors. The overall CASP scores ranged from 11 to 21, which indicated moderate to good study quality. MSDs remained a critical occupational health issue among nurses globally. Implementation of ergonomic interventions, workload management, and ongoing occupational health surveillance were the key strategies to reduce injury burden and improve workforce sustainability.